If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -6s + 7 Reorder the terms: 3 = 7 + -6s Solving 3 = 7 + -6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '6s' to each side of the equation. 3 + 6s = 7 + -6s + 6s Combine like terms: -6s + 6s = 0 3 + 6s = 7 + 0 3 + 6s = 7 Add '-3' to each side of the equation. 3 + -3 + 6s = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 6s = 7 + -3 6s = 7 + -3 Combine like terms: 7 + -3 = 4 6s = 4 Divide each side by '6'. s = 0.6666666667 Simplifying s = 0.6666666667
| 0.6x^2=9x^2-1.7 | | 1/(4-x)+1/(2+x)=3/4 | | Ln(5)(8)= | | 4x+4x=2x+10 | | 2XY+4X=6 | | y+1.6=14.4 | | 6x(8x+7)= | | 11z=z+10z | | 65/8+27/8 | | -6/7-1/4 | | -1/2+1/3 | | 8/9-7/12 | | 6/7+3/5 | | 2+3y=6y-1/2 | | 1/5+1/10 | | 8/9+1/4t=2 | | 7*(-6)= | | 0.1(0.1x+0.7)=-0.7 | | 5x-9x-12=-4x+7-12 | | -2/5-2-7 | | 7x(-6)= | | 1/3(2x-6)=4 | | 6/5+4/5x=51/20+7/4x+3/4 | | (2v-9)(8-v)=0 | | 8=-2/x | | 2(2y-7)+20=54-8y | | 3/11=n/33 | | 11=5+2/3b | | 4+3y-3=6y+7-2y | | a-3.54=8.70 | | 8x+8.52=2x+18 | | -6y=2.46 |